Keterkaitan Alexithymia dengan Perilaku Agresif pada Remaja Laki-Laki - Siti Nurfitria; Iin Inayatul Machsunah (International Consortium of Education and Culture Research Studies, 2019)
In 2018, KPAI noted that 84% of students in Indonesia had experienced violence at school. The research conducted by Jannah (2018) on early adolescents at Surabaya A Junior High School revealed that 76% of students had hit, 66% had fought, 46% had damaged items when angry, 90% had been hostile, 84% were angry and indicated adolescents tend to be prone to aggressive behavior. Adolescents who are male have a tendency to behave aggressively higher when compared to women (Santrock, 2007). The development of impulsive aggression involves emotional processes (Teten et al, 2008). Emotional states during adolescence are characterized by unstable and turbulent emotions, so that the mood can change quickly. Teenagers are said to have reached emotional maturity if they do not